Implementasi Model Si-UUL dalam Pembelajaran Berbicara pada Anak Speech Delay di TK Nusantara Bekasi - Rini Kurniawati; Sri Watini (Jurnal Studi Guru dan Pembelajaran, 2024)
Speech ability is a crucial part in a child’s language development, which has significant impact on their future intellectual and social development. At TK Nusantara Bekasi, within the past two years there were 10%-12% students with speech delay, and two of them were 5-6 years old and have never had any speech therapy by experts. This research aims to describe the Implementation of Model Si-UUL (Simak Ucap Ulang) as an innovative strategy to deal with speech development issues in children aged 5-6 years old with speech delay at TK Nusantara, Bekasi, held in September-December 2023. Method of research used is qualitative descriptive with data collecting through interviews, documentation, and notes. Research result shows that research subjects have functional speech delay, i.e. expressive speech disorder caused by the lack of stimulus or wrong parenting. Implementation of Model Si-UUL affects the speech ability of children with speech delay, from the indicator of verbal expressive language achievement it is observed that children are capable of conveying their feelings and ideas using suitable words when communicating and able to participate in a dialogue.